2016
DOI: 10.12806/v15/i3/r1
|View full text |Cite
|
Sign up to set email alerts
|

What’s Up with This Leadership Thing? Voices of African American Male College Undergraduates

Abstract: This study investigates the perceptions of leadership of African American undergraduate males who attend a predominately-White institution in the Southwest after participation in a leadership development program. Research concerning African American undergraduate males in education has been from a deficit-orientated narrative and focused primarily on academic achievement or lack of involvement, with little attention paid to African American males performing leadership. As society continues to focus on graduati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Researchers continuously find that joining a fraternity and participating in an ethnic student organization are significant to Black and Latino college men’s leadership development (Garcia et al, 2017; Guardia & Evans, 2008; Harper & Quaye, 2007; Preston-Cunningham et al, 2016). Given our focus on students’ engagement and leadership in a male-centered program, this study has implications for ways to broaden leadership opportunities for Black and Latino college men through both on- and off-campus contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers continuously find that joining a fraternity and participating in an ethnic student organization are significant to Black and Latino college men’s leadership development (Garcia et al, 2017; Guardia & Evans, 2008; Harper & Quaye, 2007; Preston-Cunningham et al, 2016). Given our focus on students’ engagement and leadership in a male-centered program, this study has implications for ways to broaden leadership opportunities for Black and Latino college men through both on- and off-campus contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also find that Black and Latino men's engagement on campus provides important opportunities for bonding and a heightened sense of connectedness (Baker, 2013;Brooms et al, 2018Brooms et al, , 2021Strayhorn, 2008). Specifically related to leadership, studies show that leadership opportunities contribute to Black and Latino men's growth, identity, collective orientations, and sense of community (Brooms et al, 2018;Garcia et al, 2017;Hotchkins & Dancy, 2015;Preston-Cunningham et al, 2016;Sutton & Terrell, 1997). The Latino male participants in Garcia et al's (2017) study reported gaining self-confidence and learned to work as a team through engaging in Greek letter organizations, ethnic student organizations, and internship programs.…”
Section: Black and Latino Men's Engagement And Leadershipmentioning
confidence: 99%